Southern Africa’s Morphing into a MICE Tourism Space: Critical Insights for Institutional Investors - Zibanai Zhou (Springer, Cham, 2022)
The chapter analyses the state of MICE tourism and available MICE investment opportunities in southern Africa. It examined challenges confronting southern Africa in its resolve to diversify the mono-cultural regional economy. The analysis was framed within the contingency management perspective. An interpretive qualitative methodology was used to collect data from 60 self administered questionnaires and five in depth interviews. MICE stakeholders were chosen through a simple random selection process. Results suggested that MICE tourism in southern Africa is at its formative stage albeit with potential for further growth. Southern Africa has competitive MICE amenities and emerging as a MICE investment destination laden with immense potential. Southern Africa MICE tourism’s future growth trajectory will depend on the adopted MICE management responsive strategy to the challenges affecting the region. The region could leverage on the Approved Destination Status (ADS) dispensation as a way of diversifying its MICE tourism market. Southern African countries can also re-configure their MICE product offerings and review tourism juristic bodies’ funding model to strengthen and position the region on the global MICE stage.